Active and passive utility of search interface features in different information seeking task stages - Huurdeman, Hugo C.; Wilson, Max L.; Kamps, Jaap (2016)
Models of information seeking, including Kuhlthau’s information Search Process model, describe fundamentally different macro-level stages. Current search systems usually do not provide support for these stages, but provide a static set of features predominantly focused on supporting micro-level search interactions. This paper investigates the utility of search user interface (SUI) features at different macro-level stages of complex tasks. A user study was designed, using simulated work tasks, to explicitly place users within different stages of a complex task: pre-focus, focus, and post-focus. Active use, passive use and perceived usefulness of features were analysed in order to derive when search features are most useful. Our results identify significant differences in the utility of SUI features between each stage. Specifically, we have observed that informational features are naturally useful in every stage, while input, control features decline in usefulness after the pre-focus stage, and personalisable features become more useful after the pre-focus stage. From these findings, we conclude that features less commonly found in web search interfaces can provide value for users, without cluttering simple searches, when provided at the right times.